The study of dynamic modulus thermal analysis on different types of polymer / Fadiatul Hasinah Muhammad - Muhammad, Fadiatul Hasinah (2007)
This study was conducted to determine dynamic mechanical properties for different types of pure polyethylene like high density polyethylene (HDPE) and low density polyethylene (LDPE) with references to frequency and temperature. Temperature scan in the range of (-120°C to 150°C) were performed and determined with Perkin Elmer DMA-7 in three point bending mode. Storage modulus (E'), loss modulus (E") and mechanical loss factor (tan 5) were recorded during testing. Storage modulus (E'), loss modulus (E") were found to be decreasing whereas the mechanical loss factor (tan 8) increasing due to temperature employed. Storage modulus (E') for high density polyethylene (HDPE) is higher than low density polyethylene (LDPE) because the molecular chain for high density polyethylene (HDPE) consists of lower degree of branching. It also observed that as frequency increase, the values of tan 5 and loss modulus (E") decrease whereas the value of storage modulus (E') increase in the case of both high density polyethylene (HDPE) and low density polyethylene (LDPE).